Motivation of U.S. High School Students in Learning Chinese - Zhao, Suihua; Wu, Yiqiang (Advances in Social Sciences Research Journal, 2024)
This study surveyed 217 American high school students’ motivational factors in learning Chinese and the factors that sustain their learning of this language. In addition, the perceptions of teachers and student focus groups were used to verify, explain and expand the survey findings. Due to the constraint of the space, only quantitative research data and findings are included in this paper. The qualitative research data and findings will be discussed in the future. The findings suggested that the future career prospect connected to China’s economy was one of the most important factors that motivated students to learn Chinese and sustained their motivation. This finding supports the language globalization hypothesis proposed by Dörnyei and Csizer (2002) as such that Chinese is in the process of being changed into a world language due to the growth of China’s economy. In addition, the unique aspect of Chinese language and culture contributes to the challenge of learning Chinese and serves as another important factor to motivate students and sustain their learning. This finding supports self-determination theory (SDT) as learning a challenging subject satisfies learners’ needs for competence. It was found non-Chinese students continued significantly longer in Chinese programs. Heritage is ethnic Chinese students’ most important motivator to learn Chinese and to sustain their learning. The desire to maintain one’s heritage through learning a second language (L2) reflects heritage learners’ need for relatedness to their culture, which is one of human beings’ innate psychological needs according to SDT. More studies on high school students’ motivation for learning Chinese and other less commonly taught languages are needed. This research is intended to provide data for schools in the United States and overseas that are contemplating implementation of a Chinese language program.